Potencial bioterapêutico dos probióticos nas parasitoses intestinais - De Oliveira-Sequeira, Teresa Cristina Goulart [UNESP]; Ribeiro, Cláudia Mello [UNESP]; Gomes, Maria Isabel Franchi Vasconcelos [UNESP] (FapUNIFESP (SciELO), 2008)
Probiotics are live microorganisms which, when administered in adequate amounts, beneficially affect the general health status of man and animal. The great interest in probiotic microganisms is based on evidences from clinical studies indicating benefits in the prevention or treatment of a broad spectrum of gastrointestinal and systemic disorders. The potential mechanisms by which probiotics beneficially affect health include strengthening of the intestinal barrier, modulation of the immune response, and antagonism of pathogens either by the production of antimicrobial compounds or through competition for mucosal binding sites. In some specific clinical circumstances, there is clear evidence of benefit whereas in others, the results are dubious and important questions remaining unanswered. The aim of this review article is to focus probiotics on their potential as biotherapeutic agents against intestinal parasites.
Probiotics as potential biotherapeutic agents targeting intestinal parasites
Keywords: Probiotics; Therapeutic use; intestinal parasites